A case of acquired tufted angioma in adulthood - Filippo Pesapane; Gianluca Nazzaro; Silvia Alberti-Violetti; Raffaele Gianotti (Sociedade Brasileira de Dermatologia, 2015)
AbstractTufted angioma is a rare vascular tumor whose name derives from its histopathological appearance, characterized by tufts of capillaries within the dermis. Its etiology and pathogenesis are uncertain. Tufted angioma typically occurs during infancy or early childhood and displays various clinical patterns. It may present as a subtle stain-like area that later thickens as a large plaque, infi ltrated or dusky blue-purple lesion, or as an exophytic, fi rm, violaceous, cutaneous nodule. Medical treatment is not necessary for tufted angioma, given its benign nature and slow progression. Only clinical follow-up is therefore recommended.